Berlin Squirrelpox Virus, a New Poxvirus in Red Squirrels, Berlin, Germany - Wibbelt, Gudrun; Tausch, Simon H.; Dabrowski, Piotr W.; Kershaw, Olivia; Nitsche, Andreas; Schrick, Livia (Emerging infectious diseases, 2017)
Near Berlin, Germany, several juvenile red squirrels (Sciurus vulgaris) were found with moist, crusty skin lesions. Histology, electron microscopy, and cell culture isolation revealed an orthopoxvirus-like infection. Subsequent PCR and genome analysis identified a new poxvirus (Berlin squirrelpox virus) that could not be assigned to any known poxvirus genera.